Solar energy conversion an introductory course - Dixon, A. E. 1938- (Arthur Edward).; Leslie, J. D. 1935- (James D.). (Toronto Pergamon Press, 1979)
Solar Energy Conversion: An Introductory Course is a collection of papers that deals with the technical, mechanical, and operation concerns in converting solar energy. The title first details solar radiation, and then proceeds to discussing solar collectors. Next, the selection covers selective surfaces and the thermal regulation of buildings. The text also talks about planning of solar architectures. The next part tackles topics about the direct conversion of solar energy. Part VII discusses the control and measurement of collected solar energy, while Part VIII covers bioconversion and biomass. The book will be of great use to engineering and science students. Professionals involved in the research and development of solar technology will also benefit from the text.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Solar energy; Electronic books